SOSIALISASI PERATURAN DAERAH NO. 11 TAHUN 2018 TENTANG PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DI PROVINSI KALIMANTAN SELATAN - Erini Junita Sari; Hanifah Hanifah (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to increase public understanding of Regional Regulation (Perda) No. 11 of 2018 concerning Women's Empowerment and Child Protection in South Kalimantan. The program was conducted to address the limited public awareness regarding women's rights, child protection, and the available reporting mechanisms for cases of violence, discrimination, and abuse. The activity employed interactive socialization through lectures, discussions, question-and-answer sessions, and case studies to encourage participants' active involvement. The results indicated an improvement in participants' knowledge and awareness of the importance of protecting women and children, understanding their legal rights, and recognizing the appropriate institutions and procedures for reporting cases of violence and child abuse.